Usefulness of computed tomography venography in gynecologic cancer patients with lower extremity edema. Issue 37 (11th September 2020) - Kim, Won Jun; Kim, JaYoung; Kang, Minsoo; Park, Dae Hwan; Jeon, Jae Yong
Abstract : Abstract: Lower extremity (LEx) edema is a common complication in gynecologic cancer patients. There are 2 main causes of edema in these patients such as deep vein thrombosis (DVT) and lymphedema. Early diagnosis and treatment of DVT are certainly important, but it is often difficult to evaluate proximal DVT by using ultrasound. The aim of this study is to demonstrate the usefulness of computed tomography venography of the lower extremity (CTV LEx) for the diagnosis of the DVT and investigate predictive factor of DVT in gynecologic cancer patients with LEx edema. The medical records of 415 gynecologic cancer patients who were referred to the department of rehabilitation medicine with LEx edema were retrospectively reviewed in this case-controlled study. We categorized CTV LEx findings as follows: DVT proximal to the inguinal ligament (inferior vena cava or iliac vein thrombosis) and DVT distal to the inguinal ligament (femoral, popliteal, or calf vein thrombosis). We also evaluated patient characteristics including D-dimer level. We analyzed the correlation of each factor with DVT frequency and used receiver operating characteristic curve analysis to determine the appropriate D-dimer threshold. Sixty-six patients were diagnosed with DVT; of them, 35 (53%) had DVT proximal to the inguinal ligament. Twenty-two patients were diagnosed with pulmonary embolism, of whom 15 had proximal DVT. Patients with proximal DVT tended to have pulmonary embolism ( P < .001). Distal organ metastasis (odds ratio [OR], 2.88; P = .002) and a high D-dimer level (OR, 1.13; P = .001) were correlated with DVT. CTV LEx is a useful diagnostic tool for gynecologic cancer patients with LEx edema, particularly high-risk patients, that should be performed at the initial evaluation.